Implementation of Positive Behaviour Support (PBS) in Inclusive Education - Iriyani, Dania Rithma Danti; Santosa, Achadi Budi; Zuhaery, Muhammad (Edunesia : Jurnal Ilmiah Pendidikan, 2025)
Inclusive education is one of the efforts in education that plays a role in eliminating discrimination, one of which is by removing barriers between students with special needs and those without. PBS is one of the methods used in inclusive education to address issues that arise in the educational process, which usually involves students with special needs. This research aims to describe the implementation of PBS in the context of inclusive education using a qualitative approach through interviews with several informants to explore the implementation of PBS, its impact on the learning environment, and the challenges faced. The study results indicate that implementing PBS involves several stages and fosters positive character within the educational unit. The learning environment becomes more inclusive and conducive, marked by increased mutual respect, empathy, and student cooperation. PBS also contributes to improving the academic achievement of students with special needs and reducing negative behavior in schools. Challenges were also found within the educational unit, which need to be addressed to ensure the sustainability of the PBS program.